Revolutions and revolutionary movements - DeFronzo, James; Taylor & Francis (Online service). (Boulder, Colorado Westview Press, A Member of the Perseus Books Group, 2019)
"With crucial insights and indispensable information concerning modern-day political upheavals, Revolutions and Revolutionary Movements provides a representative cross section of the most significant revolutions of the twentieth and twenty-first centuries. This Fifth Edition is revised and updated with a new chapter on the Arab Revolution from its beginning in December 2010 to the present. In this widely used text, students can trace the historical development of eleven revolutions using a five-factor analytical framework. Author James DeFronzo clearly explains all relevant concepts and events, the roles of key leaders, and the interrelation of each revolutionary movement with international economic and political developments and conflicts, including World Wars I and II, the Cold War, and the War on Terror. Student resources include multiple orienting maps, summary and analysis sections, suggested readings, chronologies, and documentary resources"-- Provided by publisher.
Machine generated contents note: List of Maps -- Preface -- Acronyms -- Introduction -- 1. Social Movements and Revolutions -- 2. The Russian Revolutions and Eastern Europe -- 3. Revolution In China -- 4. The Vietnamese Revolution -- 5. The Cuban Revolution -- 6. Revolution In Nicaragua -- 7. The Iranian Revolution and Islamic Fundamentalism -- 8. Islamic Revolutionary Movements -- 9. South Africa -- 10. Revolution Through Democracy -- 11. The Arab Revolution -- 12. Conclusions -- Sources for Documentary Films -- About the Author -- Index.
Includes bibliographical references and index.
Keywords: Electronic books; Revolutions; Social movements; Revolutions -- Case studies; World politics -- 20th century; World politics -- 21st century; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Government / International; SOCIAL SCIENCE / Sociology / General